Endothelin-1 Promotes Osteosarcoma Cell Invasion and Survival against Cisplatin-induced Apoptosis - Zhao, Yuanting (Springer-Verlag, 2011)
BACKGROUND: Endothelin-1 (ET-1) participates in a wide range of cancer-relevant processes including cell proliferation, inhibition of apoptosis, matrix remodeling, bone deposition, and metastases. Although ET-1 reportedly promotes osteosarcoma (OS) cell invasion, suggesting an important role of ET-1 in OS metastasis, the role of ET-1 in OS remains unclear. QUESTION/PURPOSES: We asked whether (1) ET-1 expression is associated with the malignancy of OS, (2) ET-1 enhances the cell invasion ability of OS, and (3) ET-1 promotes OS cell survival against apoptotic stress. METHODS: We cultured primary OS specimens from 22 patients with Stages II (OS-II) and III (OS-III) in real-time quantitative RT-PCR and ELISA to compare ET-1 expression. We used Transwell(®) cell invasion assays (in triplicate) to assess the invasion ability of cells in the presence or absence of exogenous ET-1 and/or ET receptor antagonists. We compared cell apoptosis rate among the cells treated with cisplatin in the presence or absence of exogenous ET-1 and/or ET receptor antagonists. We used OS cell line MG-63 in all experiments as a reference. RESULTS: Real-time quantitative RT-PCR and ELISA showed OS-III cells had greater ET-1 expression than OS-II cells at the mRNA and the secreted protein levels. Transwell(®) cell invasion assays showed OS-III cells had a greater migrated cell number than OS-II cells, which could be abrogated by ET(A) receptor antagonist BQ123 (100 pmol/L), but not ET(B) receptor antagonist BQ788 (1 μmol/L); exogenous ET-1 dose-dependently promoted OS cell migration, which could be inhibited by BQ123 (100 pmol/L). Cisplatin (10 nmol/L) induced less apoptosis in OS-III cells than in OS-II cells; exogenous ET-1 dose-dependently promoted OS cell survival against cisplatin-induced apoptosis; both effects were reversed by BQ123 (1 μmol/L), but not BQ788 (1 μmol/L). CONCLUSIONS: Increased ET-1 expression appears to be associated with increased malignancy of OS. ET-1 promotes OS cell invasion and survival against cisplatin-induced apoptosis through the ET(A) receptor. CLINICAL RELEVANCE: The ET-1/ET(A) pathway may represent an important target for treating OS, because blocking the ET(A) receptor with a selective antagonist can inhibit OS cell invasion and potentiate a chemotherapeutic agent’s effect on OS.